The - Patterson, Thomas E. (McGraw Hill, 2006)
This comprehensive text is known for its engaging narrative and its positive presentation of the latest developments in scholarship and real-life politics. Through the use of narrative, The American Democracy weaves together theory, information, and examples in ways that highlight key points, make them easy to understand, and capture readers' interest. The Texas edition includes eight additional chapters that examine the government and politics of the Lone Star State including the Texas State Constitution, interest groups, political parties and elections, the legislature, the governor and state agencies, the court system, and local government in Texas.